(untitled) (South East Asia Journal of Public Health, 2015)
In India, the National Rural Health Mission envisaged of having committees with civil society representation at all publicly financed hospitals known as Rogi Kalyan Samiti (RKS), with mandate to enhance governance in hospitals. There are limited evidences about functioning of these committees in many states, especially in North Eastern (NE) states. This paper analyses the perspective of RKS members and relate to changing community- health system structure for improved governance. The study was conducted in three states Manipur, Meghalaya, and Tripura of NE Region of India. Using stratified sampling design, 14 RKS/facilities were selected from Manipur, 15 from Meghalaya and 11 from Tripura. Two key informants (mainly, president/secretary of RKS) were interviewed using a semi-structured pre-tested questionnaire in local language. The major areas of RKS operationalization identified include; constitution, finance management and activities related to health systems strengthening. RKS was constituted during 2006-07 with governing body following issuance of government of India guidelines. The funds (grants and User Fee) were utilized for purchase of furniture, bio-medical waste management etc. The governing body meetings focused mainly on ensuring services; in Tripura 72% of RKS had regular meetings and have shown improvement in functioning of facilities.Formation of RKS model paved way to a new beginning for strengthening health system with involvement of local leaders, civil society to improve governance. The functioning is derived by availability of resources, capacity of committee members and the bureaucratic process. Revision in functioning of RKS model is essential towards self-sustainability and bridge between community-health systems. South East Asia Journal of Public Health Vol.4(2) 2014: 16-22